Empowering the community or escape daily routine - a voluntourism perspective - Abreu, José (2021)
On the edges of tourism, volunteering, and travel, we find voluntourism with tourists, mainly from high-income countries, looking for an alternative form of travel that promises sustainable development of destinations. The aim of the paper is to explore voluntourism through motivations and impacts, as well as aggregate different volunteers in categories, in order to better understand this phenomenon. The results of a questionnaire answered by 65 international volunteers show seven motivations and a lack of attention on the local projects. More than half of the volunteers are considered to have short participations in projects, considering the destination as a very important aspect, have minimal skills, and have a passive participation, as a minimal direct contribution. Generically, our research may help to highlight and boost the voluntourism experience, creating positive and transformative changes.